Bio-Guided Optimization of Cystoseira abies-marina Cosmeceuticals Extraction by Advanced Technologies - Gonçalo P. Rosa; Andreia F. Peixoto; Maria Carmo Barreto; Ana M. L. Seca; Diana C. G. A. Pinto (Marine Drugs, 2022)
Cystoseira abies-marina (reclassified as Gongolaria abies-marina) is a brown seaweed species rich in meroterpenoids, presenting interesting antioxidant, antitumor, and anti-inflammatory activities. However, there is still a lot to uncover regarding the bioactive potential of this species, as evidenced by the lack of records of antiaging activities from Cystoseira abies-marina, making this macroalga an excellent candidate for studies of its cosmeceutical potential. Ultrasound-(UAE) and microwave-assisted extraction (MAE) are advanced sustainable technologies that are very efficient in enhancing bioactive compound extraction. Applying these extraction techniques to a new biological matrix often calls for optimizing the parameters toward the best extraction yield. Since Cystoseira abies-marina is a new matrix for both UAE and MAE techniques, the present work proposes the optimization of the extraction process, using a novel approach: instead of only focusing on increasing the yield, the goal of this work is to determine the parameters for UAE and MAE that lead to extracts with better antiaging activities. For this bio-guided approach, several Cystoseira abies-marina extracts were prepared by UAE and MAE under varying conditions of solvent, time, and algae/solvent ratios. Their antiaging activities were then determined, and all the results combined to unveil the conditions yielding extracts with higher cosmeceutical potential. Using statistical tools, it was found that, for UAE, the best conditions were ethyl acetate, 15 min, and a ratio of 1:4, which led to an extract with high yield, and causing the strong inhibition of tyrosinase and elastase. In turn, ethanol, 10 min, and a ratio of 1:4 were the best conditions for MAE, leading to the extract with the best antioxidant activity. The results show that the proposed bio-guided approach was effective in obtaining extracts with high cosmeceutical potential, unveiling the possibility of modulating an extract’s activity by changing the extraction method.